Tau protein as a regulator of mitochondrial function and dynamics - Eleni Tsakiri; Carlos Campos-Marques; Christina Ploumi; Kalliopi Skourti; Antonis Roussos; Eirini Mytilinaiou; Anastasia Vamvaka Iakovou; Ildete Luísa Ferreira; Chrysoula Dioli; Despoina D. Gianniou; Martina Samiotaki; Jonas Campos; et al. (Proceedings of the National Academy of Sciences, 2026)
Mitochondrial damage is a shared hallmark of brain aging and neurodegeneration. While pathological Tau mutations disrupt mitochondrial dynamics and function, the physiological role of wild-type (WT) Tau in the maintenance of mitochondrial homeostasis remains poorly understood. Here, using Caenorhabditis elegans and mice lacking PTL-1, the nematode Tau-like homolog, and Tau respectively, we demonstrate that Tau deficiency promotes a shift toward a pro-fusion mitochondrial state associated with enhanced mitochondrial function and stress resistance. In both models, loss of Tau leads to increased mitochondrial activity and altered redox homeostasis, while it enhances resistance to heat and mitochondrial stress in C. elegans . Strikingly, loss of FZO-1, the mitofusin homolog, abolishes the beneficial phenotypes, whereas its overexpression phenocopies key aspects of Tau/PTL-1 deficiency. Together, our findings uncover a conserved role for WT Tau in restraining mitochondrial fusion and functional adaptation, highlighting its contribution to mitochondrial homeostasis and cellular stress responses.